Evaluasi Peraturan Daerah Nomor 8 Tahun 2005 tentang Pelarangan Prostitusi terhadap Praktik Prostitusi di Kecamatan Karawaci Kota Tangerang - Siti Nur Intan Soraya; Sapto Nugroho, Kandung; Maisaroh , Ima (Epistemik Press, 2024)
Prostitution is a sexual relationship between men and women without being bound by a legal marriage. The practice of prostitution continues to be a problem until now and has become one of the professions and business fields for economic purposes. If left unchecked, it will cause an increase in the number of sexually transmitted diseases. The formulation of the problem in this study is how to evaluate the Tangerang City Regional Regulation Number 8 of 2005 concerning the Prohibition of Prostitution. The research method in this thesis is a qualitative descriptive approach, this study uses analysis through interviews, observations, and document studies. The theory used in this study is the policy evaluation theory according to William N. Dunn (2003:610) which consists of 6 components, namely effectiveness, efficiency, adequacy, equality, responsiveness and accuracy. Based on the results of the study on the evaluation of the Tangerang City Regional Regulation Number 8 of 2005 concerning the Prohibition of Prostitution, its implementation has run smoothly, but there are several things that need to be optimized comprehensively in terms of effectiveness, during the process of enforcing this Regional Regulation, information leaks often occur which cause PSKs not to be optimally caught. Next, efficiency, Guidance carried out in the form of overcoming the negative impacts of Regional Regulation Number 8 of 2005 seems less than optimal due to the limited capacity of the Shelter House and the existence of equality, in the implementation of Tangerang City Regional Regulation Number 8 of 2005, namely in the Regional Regulation only regulates perpetrators of the opposite sex, but perpetrators of the same sex are not regulated in the Regional Regulation. Many perpetrators of the same sex or homosexuals also violate the Regional Regulation. If left alone, it is possible that this will happen which will increase the number of sexually transmitted diseases. In this component, the implementation of Tangerang City Regional Regulation Number 8 of 2005 concerning the Prohibition of Prostitution in Karawaci District seems smooth, but in reality it has not run with optimal results.